Development of Supplementary Science Teaching Materials with Ethnoscience Contained to Foster Students' Critical Thinking - Kumalasari, Lina; Sudarmin, Sudarmin; Sulistyorini, Sri (Journal of Primary Education)
The purpose of this study is to develop teaching materials containing ethnoscience as well as the feasibility and effectiveness of natural science teaching materials supplement containing ethnoscience to foster students' critical thinking. This study applied development technique of ADDIE that consists of five stages: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation (ADDIE). The subjects of this study were grade IV elementary school students in Temanggung. The research instruments were observation, questionnaire, test, and documentation as data collection instruments. Analysis of the data from the N-gain test and t-test were used to find out the improvement in learning outcomes and critical thinking. The results show that the supplement of science teaching materials was appropriate to be used based on the expert validation test. The results of the product trial, natural science teaching materials supplement show an improvement in learning outcomes based on an N-gain value of 0.648. The effectiveness test of supplementary science teaching materials with ethnoscience contained show that it is effective in fostering critical thinking skills of student.